Bank Profitability and Risk-Taking under Low Interest Rates - Jacob A. Bikker; Tobias M. Vervliet (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
The aim of this paper is to investigate the impact of the unusually low interest rate environment on the soundness of the US banking sector in terms of profitability and risk-taking. Using both dynamic and static modeling approaches and various estimation techniques, we find that the low interest rate environment indeed impairs bank performance and compresses net interest margins. Nonetheless, banks have been able to maintain their overall level of profits, due to lower provisioning, which in turn may endanger financial stability. Banks did not compensate for their lower interest income by expanding operations to include trading activities with a higher risk exposure.
Keywords: 330; profitability; risk-taking; low interest rate environment; (dynamic) panel data models